Instrumento de avaliação de texto narrativo em língua de sinais: uma versão para o uso no ambiente escolar - Montes, Aline Lucia Baggio (2023)
Sign languages, in general, have all levels of complexity and expressive power of oral languages, from the phonetic to the discursive level. However, all the plurality present in its structure cannot be noticed in the narrative speeches of countless deaf children who, given the absence of proficient deaf and hearing interlocutors, are harmed in the process of development and even language acquisition. This scenario results in a significant delay in the development of these children's language skills, sometimes well below expectations for their age. The instrument for evaluating narrative texts in sign languages was developed by Jarque and collaborators (2018) to analyze the narratives of deaf students in Catalonia/Spain, called Valoración de Narrativas en Lengua de Signos – Lengua de Signos Catalana/Producción (NarVaL-LSC/Prod). One of the Brazilian collaborators (LACERDA, 2020) carried out the translation of the instrument and adaptation for use in Brazil, called Evaluation of Narratives in Brazilian Sign Language/Production (NarVaL-Libras/Prod) with the objective of helping teachers of deaf students and specialists of the area to know the structure of the narratives elicited by their students, as well as to describe/score the identified formal elements and follow the development of the narratives in Sign Languages. Thus, this research aims to propose an illustrated version, through videos, of NarVaL-Libras/Prod (NarVaL-Libras/Prod-Ilustrado) for use in the school environment. Based on a corpus of narratives by deaf adults, short videos were created, made available by reading QR Codes and hyperlinks, exemplifying the indicators and their respective descriptors contained in the instrument, to assist the teacher in understanding and using this tool, raising awareness of the macro and microstructural aspects of Libras. Its specific objectives are the description and analysis of the linguistic resources and strategies used in the elicitation of semi-spontaneous narratives produced in Libras, to enable knowledge of the structure of the language in use, contributing especially to the training of teachers who work in the education of the deaf. and who often do not have specific language training for a detailed analysis such as that provided by NarVaL-Libras/Prod. Therefore, it is believed that the NarVaL-Libras/Prod-Ilustrado instrument can contribute to the identification of possible narrative limitations in deaf children and, thus, help as a tool in the organization of educational intervention strategies focused on overcoming delays, when found.